(untitled) (Modern Problems of Metallurgy, 2021)
Peculiarities of ore materials movement in a drum mill are considered. A mathematical model of ore materials grinding process in a drum ball mill is developed from the position of balance of energy quantities of destruction process: work of external force influence and value of internal potential energy of deformation of ore pieces. Using the finite element method, the analysis of the stress-strain state of the loading elements, the interaction of pieces of ore in the layer of particles under pressure under the condition of changes in shear and shock loads. The mathematical model allows to calculate the maximum loads in the loading elements (ore, spheres).It is shown that the loading element selected anywhere is subject to deformation by the neighboring loading elements (pieces of ore) under conditions of comprehensive non-uniform component compression by contact forces. These forces determine the appearance of maximum shear (tangential) stresses, which depend on the maximum normal stresses occurring in the pieces of rock.The results of modeling the stress-strain state of the loading elements confirmed that the use of wet grinding and dry grinding with incomplete loading creates more favorable conditions for shear compression of rock particles, which in turn leads to destructive tangential stresses exceeding the Coulomb strength. shear lines. There is a process of effective destruction of the rock, which in turn leads to a decrease in the energy consumption of the grinding process.